Hubungan Jenis Persalinan dan Prematuritas dengan Hiperbilirubinemia di RS Persahabatan - Elsa Roselina; Saroha Pinem; Rochimah Rochimah (Program Pendidikan Vokasi Universitas Indonesia, 2013)
ABSTRACT. Hyperbilirubinemia refers to an excessive level of accumulated bilirubin in the blood and ischaracterized by jaundice, or icterus, a yellowish discoloration of the skin and other organs. There are two riskfactors that related to hyperbilirubinemia. Those factors are maternal factor and neonates‟ factor. The aim ofthis research knew which variables which catagorized as maternal factor and neonates‟ factor that related tohyperbilirubinemia in Persahabatan hospital. This research used medical records from 216 neonates andhis/her mother from October 2008 until October 2009 as samples. Research design was case control, with used5% level of significant and 80% power. The statistical analysis was multivariable logistic regression. Factorsthat related to hyperbilirubinemia in Persahabatan hospital were type of labor (p value 0.000) andprematurity (p value 0.022). Type of labor is a dominant variable that related to hyperbilirubinemia andneonates from un-spontaneous labor has probability to be hyperbilirubinemia 50.193 times than neonates fromspontaneous labor after controlled by prematurity (odds ratio 50.193).Keywords: hyperbilirubinemia, type of labor, prematurity